Facing the Future: Concluding Remarks - Koundouri, Phoebe; Birol, Ekin; Ezel, Cahit (Springer-Verlag Berlin, 2011)
This concluding chapter proposes a holistic way forward for water resources management in Cyprus within the framework of the European Union (EU) Water Framework Directive, given the climatic, hydrogeological, socio-economic, historical, political and ethical dimensions of this interesting resource allocation problem.
Keywords: Natural resource allocation problem; Holistic water resources management; Efficient and effective policies; Water Framework Directive; Single management unit